MARKETING MANAGEMENT OF ISLAMIC HIGHER EDUCATION IN INDONESIA SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS: MANAJEMEN PEMASARAN PENDIDIKAN TINGGI ISLAM DI INDONESIA SYSTEMATIC LITERATURE REVIEW DAN META-ANALISYS - Bayu Pramono; Ahmad Rifaudin; Zainal Muttaqin; Enung Nugraha; Naf'an Tarihoran (SOSIOEDUKASI, 2025)
Islamic higher education institutions in Indonesia face significant challenges in marketing management due to increasing competition and the demands of digital transformation in the era of globalization. This study aims to comprehensively analyze the implementation of marketing management in Islamic higher education through a systematic literature review and meta-analysis of empirical studies published between 2021 and 2024. The study used the PRISMA protocol methodology by analyzing five high-quality articles from the ERIC, ScienceDirect, and PubMed databases using a random-effects model for meta-analysis. The results showed that experiential marketing had the highest effectiveness with a pooled effect size of 0.82 (95% CI: 0.75-0.88, p<0.001), followed by Islamic branding with an effect size of 0.78 (95% CI: 0.72-0.84, p<0.001), marketing mix with 0.75 (95% CI: 0.68-0.81, p<0.01), digital marketing with 0.70, and social promotion with 0.68. Forest plot and funnel plot analyses confirmed the absence of publication bias and validated the reliability of the findings. The study concluded that Islamic higher education institutions should adopt a multi-strategy approach that prioritizes experiential marketing and Islamic branding as core strategies, supported by the implementation of a comprehensive marketing mix and context-specific digital marketing. This research contributes to the development of an evidence-based marketing framework that integrates Islamic values with modern marketing theory, providing practical guidance for enhancing the competitiveness of Islamic higher education institutions in Indonesia.